PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN - Yeni Puspita, 08.05.51.0027; Rijanti, Tristiana (Students Journal of Economic and Management, 2012)
This study aims to analyze the influence of leadership style, organizational culture and employee compensation to the performance of PT. Adi Setia Mitra Abadi Semarang. Type of data used in this study is the primary data is data obtained directly from the original source. While the techniques used for data collection used a questionnaire to ask a number of written questions used to obtain information and respondents. The population in this study were all employees of PT. Adi Setia Mitra Abadi, amounting to 152 people. The amount of sample used in this study based on the formula slovin inim for is 67 people. Purposive sampling technique sampling. Test equipment used in this study using the Pearson Correlation test validity, reliability testing using Cronbachalpha and test hypotheses using multiple linear regression. The analysis concluded that: (1) style of leadership has a positive effect on employee performance. The better the leadership style adopted in the company, the employees performance will also increase. (2) Cultural organizations have a positive effect on employee performance. The better the application of organizational culture, then the employees performance will be increased. (3) Compensation of employees has a positive effect on performance. The higher the compensation received, then the employees performance will be increased.Key words: leadership styles, organizational culture, compensation and employee performance